Interpreting Remote Sensing Imagery: Human Factors - Hoffman, Robert R. (CRC Press, 2009)
No matter how advanced the technology, there is always the human factor involved - the power behind the technology. Interpreting Remote Sensing Imagery: Human Factors draws together leading psychologists, remote sensing scientists, and government and industry scientists to consider the factors involved in expertise and perceptual skill.